The Hand Extending Beyond the Cosmos: Discussions on the Khalā’ [Void] Between the Baṣran and Baghdād Schools of Mu’tazila - Ahmet Mekin Kandemir (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
We can find the origins of the notion of void in the Kalām tradition’s recognition of atomism. However, the main debates on the subject appeared after the Greek philosophical heritage transitioned to the Islamic world in the 3rd century of Hijra. The literature of Kalām, just as in the metaphysical tradition, has two main types for this void being discussed. The first one is the external void (extracosmic) in which the cosmos floats. In the sources of Kalām, the question of whether such a type of void exists is debated around the questions of whether anyone who might look beyond the cosmos can see anything or whether someone who stretches their hand outside the cosmos can move it. The second type of void, which occupies more of the mutakallimūn (Muslim theologians) agenda, is the internal void (intercosmic), assumed to be within the cosmos and between the body-forming atoms. This kind of void is discussed around the question of “Whether separating the two atoms is possible so that a third one can be inserted between them?” An ongoing discussion on the intercosmic void is found between the Baṣran and Baghdād Schools of Mu’tazila. Ibn Mattawayh and al-Nīsābūrī narrated the evidence presented in these discussions in their original form. The current essay discusses the debates between the two Schools and assesses the theoretical and experimental arguments both Schools present to justify their viewpoints, considering their philosophical origins.